IMPROVEMENT OF METHODS OF MOTION COMPENSATION OF DYNAMIC OBJECTS MOVING IN VIDEO STREAM OF THE VIDEOCONFERENCING SYSTEM - Barannik, Volodymyr; Dvorsky, Mykola; Barannik, Valeriy; Himenko, Viktoria; Sorokun, Anton (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2018)
Videoconferencing gives us the opportunity to work and communicate in real time, as well as to use collective applications, interactive information exchange. Videoconferencing systems are one of the basic components of the organization of manegment, ensuring, the timeliness and necessary quality management of the implementation of objective control over the solution of the tasks. The quality of the image and the time of transmission of video information is unsatisfactory for the quality control of the troops. Considered ways to increase the efficiency of management and operational activities, due to methods of compensation of motion, using technology to reduce the volume of video data for quality improvement.